Pengembangan Bimbingan Berbasis E-Konseling Untuk Mengurangi Prokrastinasi Akademik - Sindy Claudia br Pelawi; Nyoman Dantes; Luh Putu Sri Lestari (Universitas Pendidikan Ganesha, 2022)
This study aims to develop, test the content validity, practicality of the guidebook and determine the effectiveness of the e-counseling-based guidance book with behavioral counseling theory and positive reinforcement techniques to reduce academic procrastination in students of SMP Negeri 6 Singaraja. The development procedure uses the 4D model proposed by Thiagarajan. The data in this study were collected using an academic procrastination scale which includes aspects including: 1) fear of mistakes, 2) fear of success, 3) fear of defeat, 4) fear of separation and intimacy, fear of separation and fear of intimacy). . The sample in this study were 7 students who had high academic procrastination behavior. The data analysis technique used is data analysis of the product content of the guidebook, the practicality test of the guidebook and the test of the effectiveness of the guidebook. The results showed that: 1) The assessment of the guidebook involving 3 Undiksha FIP lecturers and 2 BK teachers at SMP 6 Singaraja got the results of CVR = 22 and CVI = 0.98, 2) Practicality Test Guide involving 10 BK teachers from SMP Negeri 1, SMP Negeri 2 and SMP 6 Singaraja, the results obtained were 90.62% in the Very Practical category. 3) The effectiveness test that has been carried out using 7 students, the significance price of the pre-test score and the post-test score of 0.42 and 0.09, the significance price is 0.05. Suggestions for future researchers, there is a need for further development research on e-counseling-based guidance guidebooks for old aspects that can be changed to the latest aspects so that they are in accordance with the circumstances and development of junior high school students. Recommendations to other researchers using self-management techniques.